2008
DOI: 10.1002/aoc.1397
|View full text |Cite
|
Sign up to set email alerts
|

o‐Carboxybenzoylferrocene. Bioactivity and chemical Modifications

Abstract: The antitumor activity of o-carboxybenzoylferrocene sodium salt (1) was studied in vivo. Interaction between o-carboxybenzoylferrocene (2) and N,N -carbonyldiimidazole in boiling methylene dichloride leads to 3-(N-imidazolyl)-3-ferrocenylisobenzofuran-1(3H)-one (5). The structure of compound 5 was established by X-ray analysis. Aminolysis of compound 5 in toluene gave rise to ferrocenoylbenzamides (6a-d)-derivatives of dimethylamine, piperidine, pyrrolidine and morpholine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…All the compounds (1-12) showed low toxicity because %cell viability was above 50%. This is not surprising because it had earlier been reported that ferrocenyl derived compounds do possess low toxicity [46]- [48]. …”
Section: Resultsmentioning
confidence: 67%
“…All the compounds (1-12) showed low toxicity because %cell viability was above 50%. This is not surprising because it had earlier been reported that ferrocenyl derived compounds do possess low toxicity [46]- [48]. …”
Section: Resultsmentioning
confidence: 67%
“…The carbonyl carbon, C11 in compound 1 bends toward the iron center with a distance of 0.163 (3) from the leastsquares plane of the substituted Cp while the corresponding C11 atom in compound 2 bends slightly outward with a distance of 0.117 (4) Å from the plane of Cp. Similar bending can be seen in the N-imidazolyl derivative of compound 2 (Simenel et al, 2008). The carbonyl carbon in compound 1 lies roughly in the same plane as the substituted Cp with a torsional angle C2-C1-C11-O1 of 2.9 (2) .…”
Section: Structural Commentarymentioning
confidence: 53%
“…As seen from Table 1, carcinoma 755 is considerably more sensitive to compound 1 than Lewis lung carcinoma. This phenomenon was noted early 20, 22. The maximum level of the tumor growth inhibition, 70% as compared with controls, was observed after administration of compound 1 in the dose 2.5 mg kg −1 .…”
Section: Resultsmentioning
confidence: 82%
“…Thus, compound 1 exhibited maximum antitumor effect (carcinoma 755) at small doses. Such an inverse dose–effect response was found early for ferrocenylmethyl benzimidazole20a (Lewis lung carcinoma, dose 5.0 mg kg −1 , tumor growth inhibition 70%), ortho ‐carboxybenzoylferrocene sodium salt22 (carcinoma 755, dose 2.5 mg kg −1 , tumor growth inhibition 70%) and the other ferrocene derivatives 20c. Apparently, the found dose–efficiency dependence—the achievement of the maximum antitumor effect after application of the agent in the rather low doses—is typical for ferrocene compounds of this kind.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation